La révolution tunisienne de janvier 2011 : une lecture par les déséquilibres du territoire - Abdelkarim Daoud (EchoGéo)
Through a retrospective approach, this paper attempts to provide a reflection on the evolution of landscaping policy in Tunisia over the last four decades, and the role of unequal regional development in the outbreak of the Tunisian revolution. It stresses the need, today, for the different stakeholders to engage in a concerted dialogue into a new reading of landscape, taking into account the current and/or the expected outcome of the Revolution in order to rethink the landscaping of the national territory.